C = 1 + a + a^2 + a^3 + ... + a^n
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a; (n + 4) \(⋮\) ( n - 1) đk n ≠ 1
n - 1 + 5 ⋮ n - 1
5 ⋮ n - 1
n - 1 \(\in\) Ư(5) = {-5; -1; 1; 5}
n \(\in\) { -4; 0; 2; 6}
Bài 1 b; (n2 + 2n - 3) \(⋮\) (n + 1) đk n ≠ -1
n2 + 2n + 1 - 4 ⋮ n + 1
(n + 1)2 - 4 ⋮ n + 1
4 ⋮ n + 1
n + 1 \(\in\) Ư(4) = {-4; -2; -1; 1; 2; 4}
n \(\in\) {-5; -3; -2; 0; 1; 3}
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\)
\(a,\) Với \(n=1\Leftrightarrow5+2\cdot1+1=8⋮8\left(đúng\right)\)
Giả sử \(n=k\left(k\ge1\right)\Leftrightarrow5^k+2\cdot3^{k-1}+1⋮8\)
Với \(n=k+1\)
\(5^n+2\cdot3^{n-1}+1=5^{k+1}+2\cdot3^k+1\\ =5^k\cdot5+2\cdot3^k+1\\ =5^k\cdot2+2\cdot3^k+5^k\cdot3+1\\ =2\left(5^k+3^k\right)+5^k+2\cdot5^{k-1}+1+2\cdot3^{k-1}-2\cdot3^{k-1}\\ =2\left(5^k+3^k\right)+\left(5^k+2\cdot3^{k-1}+1\right)-2\left(3^{k-1}+5^{k-1}\right)\)
Vì \(5^k+3^k⋮\left(5+3\right)=8;5^{k-1}+3^{k-1}⋮\left(5+3\right)=8;5^k+2\cdot3^{k-1}+1⋮8\) nên \(5^{k+1}+2\cdot3^k+1⋮8\)
Theo pp quy nạp ta được đpcm
\(b,\) Với \(n=1\Leftrightarrow3^3+4^3=91⋮13\left(đúng\right)\)
Giả sử \(n=k\left(k\ge1\right)\Leftrightarrow3^{k+2}+4^{2k+1}⋮13\)
Với \(n=k+1\)
\(3^{n+2}+4^{2n+1}=3^{k+3}+4^{2k+3}\\ =3^{k+2}\cdot3+16\cdot4^{2k+1}\\ =3^{k+2}\cdot3+3\cdot4^{2k+1}+13\cdot4^{2k+1}\\ =3\left(3^{k+2}+4^{2k+1}\right)+13\cdot4^{2k+1}\)
Vì \(3^{k+2}+4^{2k+1}⋮13;13\cdot4^{2k+1}⋮13\) nên \(3^{k+3}+4^{2k+3}⋮13\)
Theo pp quy nạp ta được đpcm
\(1,\)
\(c,C=6^{2n}+3^{n+2}+3^n\\ C=36^n+3^n\cdot9+3^n\\ C=\left(36^n-3^n\right)+\left(3^n\cdot9+2\cdot3^n\right)\\ C=\left(36^n-3^n\right)+3^n\cdot11\)
Vì \(36^n-3^n⋮\left(36-3\right)=33⋮11;3^n\cdot11⋮11\) nên \(C⋮11\)
\(d,D=1^n+2^n+5^n+8^n\)
Vì \(1^n+2^n+5^n⋮\left(1+2+5\right)=8;8^n⋮8\) nên \(D⋮8\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=y^2-9\)
b: \(=m^3+n^3\)
c: \(=8-a^3\)
d: \(=\left(a-b-c-a+b-c\right)\left(a-b-c+a-b+c\right)\)
\(=-2c\cdot\left(2a-2b\right)\)
\(=-4ac+4bc\)
f: \(=\left(1-x^3\right)\left(1+x^3\right)=1-x^6\)
\(\)Tính?
\(aC = a(1+a+a^2+...+a^n)\)
\(aC = a + a^2 + ...+ a^{n+1}\)
\((a-1)C = a^{n+1} - 1\)
\(C = (a^{n+1} - 1) : (a-1)\)